2019
DOI: 10.1002/hep.30876
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial General Control of Amino Acid Synthesis 5 Like 1 Regulates Glutaminolysis, Mammalian Target of Rapamycin Complex 1 Activity, and Murine Liver Regeneration

Abstract: Background and Aims The regenerative capacity of the liver plays a protective role against hepatotoxins and impaired regeneration exacerbates liver dysfunction in nonalcoholic fatty liver disease (NAFLD). Mitochondrial bioenergetic and ‐synthetic functions are important contributory factors in hepatic regeneration, and the control of mitochondrial protein acetylation is implicated in the mitochondrial susceptibility to liver stressors. Here, we evaluated the role of general control of amino acid synthesis 5 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“… 21 Here, we tested whether ablation of GCN5L1 had the same metabolic profile in human HepG2 cells following GCN5L1 KO versus control cells cultured in Earle's Balanced Salt Solution (EBSS) with glutamine supplementation for 2 or 4 hours. Consistent with GCN5L1 LKO primary hepatocytes, 21 mTORC1 signalling was highly activated by glutamine in GCN5L1 KO HepG2 cells (Figure 3F ). Given that glutamine metabolism is critical to maintain GSH levels and cellular redox control, 26 which regulates apoptosis, we analysed cell apoptosis in HepG2 cells following GCN5L1 depletion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 21 Here, we tested whether ablation of GCN5L1 had the same metabolic profile in human HepG2 cells following GCN5L1 KO versus control cells cultured in Earle's Balanced Salt Solution (EBSS) with glutamine supplementation for 2 or 4 hours. Consistent with GCN5L1 LKO primary hepatocytes, 21 mTORC1 signalling was highly activated by glutamine in GCN5L1 KO HepG2 cells (Figure 3F ). Given that glutamine metabolism is critical to maintain GSH levels and cellular redox control, 26 which regulates apoptosis, we analysed cell apoptosis in HepG2 cells following GCN5L1 depletion.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of GCN5L1 and mitochondrial protein acetylation are significantly decreased during mouse liver regeneration. 21 To examine the expression levels of GCN5L1 in HCC, we analysed HCC tumours and adjacent liver tissues from the combined DEN and CCl 4 model (Figure S1A ). We performed immunoblot analyses of tumours and their adjacent normal liver tissues and found that GCN5L1 protein levels were decreased in DEN‐induced HCC tumours in comparison with adjacent liver tissues (Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations